Preservação e autenticidade: Etapas de um mesmo contínuo - Troitiño Rodriguez, Sonia Maria [UNESP]; Sansoni Tonello, Izângela Maria; De Carvalho Madio, Telma Campanha [UNESP] (My University, 2016)
The significant amount and variety of information that are provided by means of images, especially photographs, incite a special concern in relation to the preservation of this kind of media, in order to ensure its authenticity and sharpness and avoid its deterioration. The objectives of this study were reflecting on: 1) the concepts and definitions underpinning photographs as records; 2) the authenticity to attest what photographic records represent in its context; 3) the importance of preservation, so that the information conveyed in images may be accessed in the future. In conclusion, it can be affirmed that photographs can be constituted in archival records and therefore they should be preserved properly so that they remain, in time and space, authentic and sharp, as at the time of their production.
Preservation and authenticity of photographic records: Steps of the same continuum
Keywords: Authenticity; Photographic records; Preservation